Cradle to grave GHG emissions analysis of shale gas hydraulic fracking in Western Australia - Bista Sangita; Jennings Philip; Anda Martin (Renewable Energy and Environmental Sustainability, 2017)
Western Australia has globally significant onshore gas resources, with over 280 trillion cubic feet of economically recoverable gas located in five shale basins. The Western Australian Government and gas industry have promoted the development of these resources as a “clean energy source” that would “help to reduce global carbon emissions” and provide a “transition fuel” to a low carbon economy. This research examines those claims by reviewing existing literature and published data to estimate the life cycle greenhouse gas (GHG) pollution that would result from the development of Western Australia’s onshore gas basins using hydraulic fracking. Estimates of carbon pollution from each stage in gas development, processing, transport and end-use are considered in order to establish total life-cycle emissions in tonnes of carbon-dioxide equivalent (CO2e). The emissions estimates draw from published research on emissions from shale gas development in other jurisdictions as well as industry or government reported emissions from current technology for gas processing and end-use as applicable. The current policy and regulatory environment for carbon pollution and likely resulting GHG mitigation measures has also been considered, as well as the potential for the gas to displace or substitute for other energy sources. In areas where there is uncertainty, conservative emissions estimates have been used. Modelling of GHG emissions has been undertaken for two comparison resource development and utilisation scenarios; Australian domestic and 100% export i.e. no domestic use. Each scenario corresponds to a different proportionate allocation of emissions accounted for domestic emissions in Australia and emissions accounted for in other jurisdictions. Emissions estimates for the two scenarios are 245–502 MTCO2e/year respectively over a resource development timeframe of 20 years. This is roughly the same as Australia’s total GHG emissions in 2014 which were 525 MTCO2e/year. This research concludes that GHG emissions resulting from the development of Western Australia’s five onshore gas basins would be equivalent to all other Australian emissions sources combined at 2014 levels each year for 20 years which is the general lifetime of a well.